Molybdenum-tantalum bimetallic MOF-derived MoO 2 -Ta 2 O 5 / C composite catalyst and its application in oxidative desulfurization
The preparation of molybdenum tantalum bimetallic MOF-derived MoO2-Ta2O5/C composite catalyst by thermal reflux and in-situ calcination solves the problem of low efficiency of inactive sulfide removal by existing desulfurization technology, and achieves efficient oxidative desulfurization effect under mild conditions.
Patent Information
- Application Number
- CN202410035682.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-01-09
- Publication Date
- 2025-06-03
- Estimated Expiration
- 2044-01-09
AI Technical Summary
Existing desulfurization technologies such as HDS require high temperature, high pressure and large amounts of hydrogen, and it is difficult to effectively remove non-active sulfides, such as 4,6-DMDBT, and more efficient desulfurization technologies are needed.
The molybdenum tantalum bimetallic MOF-derived MoO2-Ta2O5/C composite catalyst was prepared by thermal reflux combined with in-situ calcination. By adjusting the calcining temperature and the metal molar ratio, a bimetal oxide/carbon material composite catalyst was formed.
It realizes ultra-deep oxidation and desulfurization of 4,6-DMDBT sulfides in fuel under mild conditions with O2 as an oxidizing agent, with a desulfurization rate of 100%, which has the advantages of good selectivity, high thermal stability and recyclability and reusability.
Smart Images

Figure CN117884114B_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of composite materials, relates to catalytic oxidative desulfurization, and particularly relates to a preparation method of a molybdenum-tantalum bimetallic MOF-derived MoO 2 -Ta 2 O 5 / C composite catalyst and its application in oxidative desulfurization. Background Technique
[0002] In recent years, with the growth of the number of automobiles, the demand for vehicle fuel has also increased significantly. However, the combustion of fuel will produce a large amount of sulfur-containing harmful substances such as SO x , SO x . The emissions of SO not only pollute the air, form acid rain, damage the atmospheric environment and threaten human health; but also cause the catalyst in the automobile exhaust treatment conversion device to be poisoned and inactivated, reducing its catalytic ability. At present, the state is strictly controlling the sulfur content in fuel (less than 10 ppm, or even sulfur-free fuel), which is of great significance for how to effectively reduce the sulfur content in fuel. The desulfurization technology adopted in industry is mainly hydrodesulfurization (HDS). HDS can effectively remove active sulfides such as mercaptans and sulfides in fuel. However, the harsh conditions such as high temperature, high pressure and consumption of a large amount of expensive hydrogen in HDS hinder its development, and the removal of non-active sulfides such as 4,6-dimethyldibenzothiophene (4,6-DMDBT) is still a difficult problem. Therefore, it is necessary to explore a more efficient desulfurization technology to solve the above problems.
[0003] Oxidative desulfurization technology (ODS) has received extensive attention from researchers due to its mild reaction conditions and high removal rate of aromatic sulfides. The commonly used oxidants in ODS mainly include hydrogen peroxide (H 2 O 2 ), molecular oxygen (O 2 ), and organic peroxides, etc. Under the action of a catalyst, the oxidant oxidizes the sulfur-containing compound into a more polar sulfone substance, and then removes it by adsorption or extraction to obtain clean fuel. Among them, designing an efficient catalyst is the core problem of oxidative desulfurization technology.
[0004] Transition metal oxides have become one of the commonly used catalysts for ODS due to their advantages such as low cost, simple synthesis process, strong Lewis acidity and good selectivity. Molybdenum-based catalysts have good catalytic activity for the removal of 4,6-DMDBT-like sulfides. In recent years, among the various ODS catalysts that have been developed, molybdenum dioxide (MoO 2 ) has become a promising catalyst. This is because MoO 2Having abundant free electrons means that a large number of unsaturated metal sites can be generated to promote the effective oxidation of sulfides. In addition, introducing another metal active component to construct a bimetallic active center is also one of the effective methods to improve the catalytic oxidation performance. Tantalum pentoxide (Ta 2 O 5 ) is an important transition metal oxide with many physical and chemical properties, and is widely used in fields such as electrocatalysis and photocatalytic degradation. It has the following advantages: high thermodynamic stability, large specific surface area, good dispersion, and abundant morphology and defect sites. At present, tantalum-based catalysts have not been widely used in oxidative desulfurization. The preparation conditions of MoO 2 are relatively harsh, and most of them are obtained by pyrolyzing precursors. Therefore, it is necessary to find a suitable precursor as a template to efficiently prepare composite catalysts.
[0005] Metal-organic frameworks (MOFs) are a class of crystalline porous functional materials formed by the self-assembly of inorganic metal centers and organic ligands. They have excellent properties such as large surface area, high porosity, adjustable pore size, high conductivity, and stability. They are considered to be multifunctional precursors for preparing various porous nanomaterials and have become a research hotspot in recent years. In addition, by selecting different metal ion sources or organic ligands, bimetallic MOFs can be synthesized or multi-metal MOFs can be formed by doping with different metal elements. Summary of the Invention
[0006] In order to solve the deficiencies in the above technologies, the purpose of the present invention is to prepare a molybdenum-tantalum bimetallic MOF-derived MoO 2 -Ta 2 O 5 / C composite catalyst by using the thermal reflux method combined with in-situ calcination.
[0007] Technical Solution
[0008] A preparation method of a molybdenum-tantalum bimetallic MOF-derived MoO 2 -Ta 2 O 5 / C composite catalyst, comprising: weighing tantalum pentachloride, 4,4-bipyridine and block copolymer polyether F127, adding them into deionized water, ultrasonically dispersing evenly, then adding sodium molybdate dihydrate, and stirring and heating under reflux at 80-160 °C, preferably 120 °C for 4-16 h, preferably 8 h; after cooling to room temperature, the substances obtained from the reaction are centrifugally washed three times with deionized water and absolute ethanol respectively, and the obtained precursor is collected, dried and ground; transferred to a magnetic ark, and placed in a tube furnace in a nitrogen atmosphere, and calcined at 300-1000 °C, preferably 800 °C with a programmed temperature increase for 1-6 h, preferably 2 h, to obtain the MoO 2 -Ta 2 O 5 / C composite catalyst.
[0009] In a preferred disclosed example of the present invention, the solid-liquid ratio of tantalum pentachloride, 4,4'-bipyridine, F127, sodium molybdate dihydrate and deionized water is 0.7 - 4.5 g: 0.1 - 1.5 g: 0.5 - 3.0 g: 0.2 - 3.5 g: 50 - 150 mL, preferably 3.6552 g: 0.7968 g: 1.0 g: 2.4439 g: 80 mL.
[0010] In a preferred disclosed example of the present invention, the ultrasonic time is 0.1 - 2 h, preferably 0.5 h.
[0011] In a preferred disclosed example of the present invention, the precursor is dried at 40 - 120 °C for 8 - 24 h, preferably dried at 60 °C for 12 h.
[0012] In a preferred disclosed example of the present invention, the molar ratio of tantalum pentachloride to sodium molybdate dihydrate is 1:0.2 - 1:10, preferably 1:1.
[0013] In a preferred disclosed example of the present invention, the heating rate of the programmed temperature rise during calcination in the tubular furnace is 1 - 10 °C / min, preferably 3 °C / min.
[0014] The obtained product is labeled as MTO / C-X, where X represents the calcination temperature (°C).
[0015] The molar ratio of metals Mo and Ta was regulated to prepare different composite catalysts for comparison, and tantalum pentachloride or sodium molybdate dihydrate in the raw materials was removed to prepare single metal oxides as the control group.
[0016] Another object of the present invention is to disclose the application of the molybdenum-tantalum bimetallic MOF-derived MoO 2 -Ta 2 O 5 / C composite catalyst in the field of catalytic oxidative desulfurization, especially the ultra-deep oxidative desulfurization of 4,6-DMDBT sulfides in fuel with molecular oxygen (O 2 ) as the oxidant.
[0017] In catalytic reactions, conventional single-metal oxide catalysts are prone to agglomeration under high-temperature calcination, reducing the utilization rate of metal atoms, resulting in fewer active sites and lower catalytic activity. To solve the above problems, in the present invention, sodium molybdate dihydrate and tantalum pentachloride are used as raw materials, and 4,4-bipyridine is used as an organic ligand to prepare MoTa-MOF by heating under reflux. Among them, 4,4'-bipyridine acts as a "pillar" in the layered structure to form an interpenetrating network, providing a stable structure for the MoTa-MOF material, while block copolymer polyether F127 is used as a structure-directing agent to induce the growth of bimetallic MOF in the solvent. Then, by means of high-temperature calcination, using MoTa-MOF as a precursor, a bimetallic oxide / carbon material composite catalyst is successfully prepared by in-situ calcination in a nitrogen atmosphere, and the effects of calcination temperature and different molybdenum-tantalum molar ratios on the crystal structure, stability, and oxidative desulfurization performance of the catalyst are studied. By changing the calcination temperature, the growth of MoO 2 and Ta 2 O 5 nanoparticles and the formation of carbon materials are induced to construct bimetallic active centers. The derived pyridyl ligands can not only obtain pyrrole N, pyridine N, and graphitic N to enhance catalytic activity, but also form a porous carbon matrix to significantly improve the dispersion and stability of metal oxide nanoparticles. In addition, the introduction of carbon materials can significantly improve the electrical conductivity of electrons, thereby accelerating the electron transfer of metal-based materials and promoting the mass transfer process. In short, this strategy not only evenly disperses metal sites, but also realizes the composite of metal nanoparticles and carbon materials, enhancing the structural stability of the composite material, and can effectively activate O 2 , which is beneficial to the efficient aerobic oxidative desulfurization of aromatic sulfur compounds in fuel under mild conditions.
[0018] Wide-angle X-ray powder diffraction (XRD), Raman spectroscopy (Raman), scanning electron microscopy (SEM), transmission electron microscopy (TEM), and high-resolution transmission electron microscopy (HRTEM) are used to analyze the crystal structure and morphological composition of the catalyst.
[0019] Using 4,6-DMDBT as a sulfur-containing substrate to prepare a model oil, and O 2 as an oxidant, the obtained catalyst is used for the catalytic oxidative desulfurization of the model oil. A gas chromatograph (GC) is used to detect 4,6-DMDBT in the model oil after the reaction, and the change in sulfur content in the model oil is calculated by the peak area to evaluate the removal performance of the catalyst for 4,6-DMDBT.
[0020] The formula for calculating the desulfurization rate is: S%=(1-C t / C 0 )×100%; where C 0 represents the initial sulfur content of the model oil, and C tIt represents the remaining sulfur content of the model oil within t (h), with the unit of ppm.
[0021] High-temperature calcination of MOF is one of the effective strategies for synthesizing metal oxide / carbon material composite catalysts. By controlling the carbonization process, the in-situ formed porous carbon material is beneficial to the chemical stability of the composite catalyst and the improvement of electron transfer. Further adopting the dual-metal design strategy in MOF can greatly improve the catalytic oxidation performance through the synergistic effect between metals, and at the same time reduce the dosage of the catalyst in the reaction; and the dual-metal can form more active sites, enhancing the ability to bind and activate O 2 to achieve the purpose of deep desulfurization of sulfur-containing compounds.
[0022] The present invention prepares a dual-metal MoTa-MOF by a thermal reflux method, and then in-situ calcines it in a nitrogen atmosphere to form MoO 2 -Ta 2 O 5 / C composite catalyst, where changing the calcination temperature is beneficial to the formation of a carbon matrix to promote electron transfer and the generation of metal oxide nanoparticles. These composite structures can achieve the uniform dispersion of MoO 2 and Ta 2 O 5 nanoparticles, increasing the exposure of effective active sites and improving the catalyst stability. By designing and developing a dual-metal composite catalyst with synergistic effect, strong recyclability and high desulfurization efficiency through a suitable method, it can achieve deep removal effects on both dibenzothiophene (DBT) and 4,6-DMDBT, and has good industrial application prospects.
[0023] Beneficial effects
[0024] The synthesis process of the present invention is simple. Using sodium molybdate dihydrate and tantalum pentachloride as raw materials, a method combining thermal reflux and high-temperature calcination is adopted. By regulating the calcination temperature and metal molar ratio, the formation of a dual-metal oxide / carbon material composite catalyst is induced, and the influence of the synergistic effect between dual-metals on the oxidative desulfurization performance is studied. The dual-metal oxide nanoparticles are uniformly dispersed in the carbon material formed by in-situ calcination, constructing dual-metal active centers, which have the advantages of good selectivity, high thermal stability and recyclability. Under mild conditions, using O 2 as the oxidant, ultra-deep removal (desulfurization rate of 100%) of the sulfur-containing compound 4,6-DMDBT can be achieved within 4 h. Description of the drawings
[0025] Figure 1 . Wide-angle XRD pattern of the MoO 2 -Ta 2 O 5 / C composite catalyst;
[0026] Figure 2 .MoO 2 -Ta 2 O 5 Raman Analysis of MoO-TaO / C Composite Catalyst;
[0027] Figure 3 .MoO 2 -Ta 2 O 5 SEM, TEM, HRTEM and Elemental Mapping Images of MoO-TaO / C Composite Catalyst, where (a) SEM image, (b-d) TEM and HRTEM images, (e-j) Mapping;
[0028] Figure 4 . Different MoO 2 -Ta 2 O 5 Comparison Chart of Catalytic Oxidation and Removal Performance of MoO-TaO / C Composite Catalysts for 4,6-DMDBT. Detailed Implementation Modes
[0029] The present invention will be described in detail below in conjunction with embodiments, so that those skilled in the art can better understand the present invention, but the present invention is not limited to the following embodiments.
[0030] Embodiment 1
[0031] A preparation method of a molybdenum-tantalum bimetallic MOF-derived MoO-TaO / C composite catalyst, comprising: weighing 3.6552 g of TaCl 2 -Ta 2 O 5 , 0.7968 g of 4,4-bipyridine and 1 g of F127 and adding them to a 250 mL round-bottom flask containing 80 mL of deionized water. After ultrasonic dispersion, 2.4439 g of Na 5 is added, and then 2.4439 g of Na 2 MoO 4 ·2H 2 O is added. The mixture is stirred and heated under reflux in an oil bath at a constant temperature of 120 °C for 8 h. After cooling to room temperature, the solid product is centrifuged and washed repeatedly with deionized water and absolute ethanol, and then dried overnight in an oven at 60 °C. The obtained precursor is placed in an agate mortar, ground into a fine powder state, and then transferred to a porcelain boat. It is calcined in a programmed temperature tube furnace under a nitrogen atmosphere at a programmed temperature to 300 °C and maintained for 2 h (the programmed temperature rate is 3 °C / min), and after natural cooling to room temperature, the composite catalyst is obtained, marked as MTO / C-300.
[0032] Embodiment 2
[0033] A molybdenum-tantalum bimetallic MOF-derived MoO 2 -Ta 2 O 5Preparation method of molybdenum-tantalum bimetallic MOF-derived MoO-TaO / C composite catalyst, comprising: weighing 3.6552 g of TaCl 5 , 0.7968 g of 4,4-bipyridine and 1 g of F127 and adding them into a 250 mL round-bottom flask containing 80 mL of deionized water. After ultrasonic dispersion, 2.4439 g of Na 2 MoO 4 .2H 2 O is added, and the mixture is stirred and heated under reflux at 120 °C in a constant-temperature oil bath for 8 h. After cooling to room temperature, the solid product is centrifuged and washed repeatedly with deionized water and absolute ethanol, and then dried overnight in an oven at 60 °C. The obtained precursor is placed in an agate mortar, ground thoroughly into a fine powder state, and then transferred to a porcelain boat. It is calcined in a programmed temperature tube furnace under a nitrogen atmosphere by programmed heating to 500 °C and maintained for 2 h (the programmed heating rate is 3 °C / min). After natural cooling to room temperature, the composite catalyst is obtained and labeled as MTO / C-500.
[0034] Example 3
[0035] Preparation method of molybdenum-tantalum bimetallic MOF-derived MoO-TaO / C composite catalyst, comprising: weighing 3.6552 g of TaCl 2 , 0.7968 g of 4,4-bipyridine and 1 g of F127 and adding them into a 250 mL round-bottom flask containing 80 mL of deionized water. After ultrasonic dispersion, 2.4439 g of Na 2 MoO 5 , 0.7968 g of 4,4-bipyridine and 1 g of F127 and adding them into a 250 mL round-bottom flask containing 80 mL of deionized water. After ultrasonic dispersion, 2.4439 g of Na 5 , 0.7968 g of 4,4-bipyridine and 1 g of F127 and adding them into a 250 mL round-bottom flask containing 80 mL of deionized water. After ultrasonic dispersion, 2.4439 g of Na 2 MoO 4 .2H 2 O is added, and the mixture is stirred and heated under reflux at 120 °C in a constant-temperature oil bath for 8 h. After cooling to room temperature, the solid product is centrifuged and washed repeatedly with deionized water and absolute ethanol, and then dried overnight in an oven at 60 °C. The obtained precursor is placed in an agate mortar, ground thoroughly into a fine powder state, and then transferred to a porcelain boat. It is calcined in a programmed temperature tube furnace under a nitrogen atmosphere by programmed heating to 800 °C and maintained for 2 h (the programmed heating rate is 3 °C / min). After natural cooling to room temperature, the composite catalyst is obtained and labeled as MTO / C-800.
[0036] For comparison, under the same conditions, composite catalysts with different molybdenum-tantalum molar ratios and single-metal oxide catalysts without adding one of the metal sources are prepared according to the above steps. The obtained products are labeled as MTO / C-800(1:10), MTO / C-800(1:5), MTO / C-800(5:1), MoO 2 and Ta 2 O 5 .
[0037] From Figure 1 the XRD patterns and Figure 2The Raman spectroscopy results show that the bimetallic molybdenum-tantalum MOF-derived MoO 2 -Ta 2 O 5 / C composite catalyst was successfully prepared by thermal reflux and high-temperature calcination. Controlling the calcination temperature can effectively regulate the formation of bimetallic oxide nanoparticles and the composite of carbon materials. When the calcination temperature is 800 °C and the molybdenum-tantalum molar ratio is 1:1, the MTO / C-800 catalyst shows the best catalytic oxidative desulfurization performance.
[0038] From Figure 3 the SEM images, it can be seen that the surface of the obtained composite catalyst is rough and fluffy. After calcination, metal oxide nanoparticles can be clearly observed in the TEM images, and an amorphous carbon layer appears in the images. From the HRTEM images, clear lattice fringes with spacings of 0.3138 nm and 0.3880 nm can be seen, corresponding to the (100) and (001) crystal planes of Ta 2 O 5 in the XRD pattern, respectively, while the lattice spacing of 0.2425 nm corresponds to the 2 crystal plane of MoO , verifying the XRD results. The Mapping images show the uniform distribution of Mo, Ta, O, C, and N elements in the MTO / C-800 catalyst, further indicating the successful synthesis of the composite catalyst.
[0039] Example 4
[0040] Application of molybdenum-tantalum MOF-derived MoO 2 -Ta 2 O 5 / C composite catalyst in oxidative desulfurization, including:
[0041] Applying the MoO 2 -Ta 2 O 5 / C composite catalysts obtained in Examples 1-3 above to catalytically oxidize and remove the aromatic sulfide 4,6-DMDBT in the model oil. The specific experimental conditions are as follows: the catalyst dosage is 0.01 g, the oxygen flow rate is 100 mL / min, 20 mL of the prepared model oil containing 4,6-DMDBT at a concentration of 200 ppm is added, and the reaction is stirred under the condition of a constant-temperature oil bath at 120 °C. After introducing oxygen, the timing starts. Samples are taken every 1 h and detected by gas chromatography (GC). The reaction stops until 4 h, and thus the removal effects of different composite catalysts on 4,6-DMDBT are obtained.
[0042] From Figure 4It can be seen that under the same reaction conditions, the removal order of different composite catalysts for 4,6-DMDBT is: MTO / C-800 > MTO / C-500 > MTO / C-300. Among them, the composite catalyst obtained at MTO / C-800 has the best performance and can completely remove 4,6-DMDBT (the desulfurization rate is 100%).
[0043] The above are only the embodiments of the present invention, and do not limit the patent scope of the present invention accordingly. Any equivalent structure or equivalent process transformation made using the description of the present invention, or directly or indirectly applied in other related technical fields, shall be similarly included in the patent protection scope of the present invention.
Claims
1. A method for preparing a molybdenum-tantalum bimetallic MOF-derived MoO2-Ta2O5 / C composite catalyst, characterized in that: include: Tantalum pentachloride, 4,4-bipyridine and block polyether F127 are weighed and added into deionized water. After being uniformly dispersed by ultrasonication, sodium molybdate dihydrate is added, and the mixture is stirred, heated and refluxed in a constant temperature oil bath at 80-160°C for 4-16 hours. After being cooled to room temperature, the substances obtained by the reaction are washed three times by centrifugation with deionized water and anhydrous ethanol respectively, and the obtained precursor is collected, dried and ground. The precursor is transferred into a magnetic ark, and placed in a tubular furnace in a nitrogen atmosphere for programmed temperature rise calcination at 300-1000°C for 1-6 hours to obtain a MoO2-Ta2O5 / C composite catalyst.
2. The method for preparing the molybdenum-tantalum bimetallic MOF-derived MoO2-Ta2O5 / C composite catalyst according to claim 1, characterized in that: include: Weigh tantalum pentachloride, 4,4-bipyridine and block polyether F127, add them into deionized water, add sodium molybdate dihydrate after ultrasonic dispersion, stir and heat under reflux in a constant temperature oil bath at 120°C for 8 hours; after cooling to room temperature, wash the obtained substance with deionized water and anhydrous ethanol by centrifugation three times respectively, collect the obtained precursor, dry and grind; transfer it to a magnetic ark, place it in a tubular furnace in a nitrogen atmosphere and calcine it at 800°C for 2 hours to obtain the product.
3. The method for preparing the molybdenum-tantalum bimetallic MOF-derived MoO2-Ta2O5 / C composite catalyst according to claim 1, characterized in that: The solid-liquid ratio of tantalum pentachloride, 4,4-bipyridine, F127, sodium molybdate dihydrate and deionized water involved in the reaction is 0.7-4.5 g: 0.1-1.5 g: 0.5-3.0 g: 0.2-3.5 g: 50-150 mL.
4. The method for preparing the molybdenum-tantalum bimetallic MOF-derived MoO2-Ta2O5 / C composite catalyst according to claim 3, characterized in that: The solid-liquid ratio of the tantalum pentachloride, 4,4-bipyridine, F127, sodium molybdate dihydrate and deionized water is 3.6552g:0.7968g:1.0g:2.4439g:80mL.
5. The method for preparing the molybdenum-tantalum bimetallic MOF-derived MoO2-Ta2O5 / C composite catalyst according to claim 1, characterized in that: The ultrasound time is 0.1~2h.
6. The method for preparing the molybdenum-tantalum bimetallic MOF-derived MoO2-Ta2O5 / C composite catalyst according to claim 5, characterized in that: The ultrasonic time is 0.5h.
7. The method for preparing the molybdenum-tantalum bimetallic MOF-derived MoO2-Ta2O5 / C composite catalyst according to claim 1, characterized in that: The precursor drying is drying the precursor at 40-120° C. for 8-24 hours.
8. The method for preparing the molybdenum-tantalum bimetallic MOF-derived MoO2-Ta2O5 / C composite catalyst according to claim 1, characterized in that: The precursor drying is drying the precursor at 60° C. for 12 hours.
9. The method for preparing the molybdenum-tantalum bimetallic MOF-derived MoO2-Ta2O5 / C composite catalyst according to claim 1, characterized in that: The programmed temperature increase is a temperature increase rate of 1 to 10°C / min.
10. The method for preparing the molybdenum-tantalum bimetallic MOF-derived MoO2-Ta2O5 / C composite catalyst according to claim 9, characterized in that: The programmed temperature increase is at a rate of 3°C / min.
Citation Information
Patent Citations
Desulfurization catalyst, preparation method thereof and method for desulfurizing hydrocarbon oil by employing same
CN105498830A
Supported magnetic modified molybdenum oxide desulfurization catalyst as well as preparation method and application thereof
CN111450837A